2021
DOI: 10.1101/2021.08.25.21262586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Willingness and influential factors of parents to vaccinate their children against the COVID-19: a systematic review and meta-analysis

Abstract: Background: Coronavirus disease 2019 (COVID-19) vaccine uptake among children will be critical in limiting the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the disease. Parents are key decision-makers for whether their children will receive a COVID-19 vaccine. Objective: To estimate parents willingness to vaccinate their children against the COVID-19, and to investigate the predictors for their decision. Methods: We followed the Preferred Reporting Items for Systematic Review… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 80 publications
(133 reference statements)
2
12
1
1
Order By: Relevance
“…shown in a recent systematic review [21]. Several socio-demographic characteristics that we found to be associated with parents' intention to vaccinate their children are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…shown in a recent systematic review [21]. Several socio-demographic characteristics that we found to be associated with parents' intention to vaccinate their children are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Several socio-demographic characteristics that we found to be associated with parents' intention to vaccinate their children are consistent with previous studies. For example, these previous studies found that significantly higher proportions of males [22][23][24], older parents [21], higher educational level [23,25] and higher income [25,26] exhibited higher intentions to vaccinate children against COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…Only one study in Turkey (Yigit et al, 2021) reported a percentage (29%) lower than the one we found. Several other studies worldwide found that parents’ intention to vaccinate their children is higher than our study and ranges from 36.7% to 72.7% (Galanis et al, 2021). In particular, studies in Europe (United Kingdom, Germany and Italy) found that the proportion of parents’ that intend to vaccinate their children ranges from 48% to 60.4% (Bell et al, 2020; Brandstetter et al, 2021; Montalti et al, 2021).…”
Section: Discussioncontrasting
confidence: 73%
“…According to a meta-analysis (Galanis et al, 2021), parents’ intention to vaccinate their children against the COVID-19 ranges from 29% to 72.7%, while the overall proportion of parents that intend to vaccinate their children is 56.8%. Parents’ willingness to vaccinate their children against COVID-19 is affected by several factors such as gender (Goldman et al, 2020; Kelly et al, 2021; Montalti et al, 2021; Yigit et al, 2021), age of parents and children (Goldman et al, 2020; Kelly et al, 2021; Montalti et al, 2021; Skjefte et al, 2021; Szilagyi et al, 2021), socio-economic status (Brandstetter et al, 2021; Hetherington et al, 2021; Kelly et al, 2021; Montalti et al, 2021; Skjefte et al, 2021; Szilagyi et al, 2021; Wang et al, 2021; Yigit et al, 2021), race (Bell et al, 2020; Kelly et al, 2021; Scherer et al, 2021; Teasdale et al, 2021), attitudes toward vaccination (Goldman et al, 2020; Kelly et al, 2021; Ruggiero et al, 2021; Skjefte et al, 2021; Yilmaz and Sahin, 2021; Zhang et al, 2020), and information about the COVID-19 (Brandstetter et al, 2021; Montalti et al, 2021; Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From early 2021, the ability to vaccinate against the COVID-19 with safe and effective vaccines is the best hope to control the pandemic (Baden et al, 2021; Haas et al, 2021; Polack et al, 2020). Unfortunately the intention to vaccinate against the COVID-19 is low not only in the general population but also among healthcare professionals with some countries showing higher hesitancy rates compared with others (Cascini et al, 2021; Galanis et al, 2020; Galanis, Vraka, Siskou, et al, 2021a, 2021b; Luo et al, 2021; Salomoni et al, 2021; Snehota et al, 2021). Moreover, several factors influence the intention to vaccinate against the COVID-19 such as socio-demographic characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%